The relevance of mobile gaming impact on the social and emotional behavior of game-addicted elementary school children: a scoping review (Poltekkes Kemenkes Bandung, 2026)
Background: The increasing prevalence of mobile game addiction has raised serious concerns regarding its impact on children’s social and emotional development. Objective: This study aimed to map and examine the relevance of mobile gaming effects on the social and emotional behavior of elementary school children using a scoping review approach. Methods: The review was conducted in accordance with the PRISMA-ScR guidelines, with article screening supported by the Rayyan tool. Literature searches were performed in ScienceDirect, ProQuest, and Wiley Online Library using the keywords “mobile gaming”, “online games”, “social impact”, “emotional impact”, “intensity”, “children”, and “elementary school children”. A total of 953 articles were initially identified. After duplicate removal, 930 articles were screened by title, resulting in 50 articles eligible for abstract screening. Subsequently, 26 articles underwent full-text review, and 9 studies met the inclusion criteria and were analyzed using narrative synthesis (Table 1). Results: The findings indicate that excessive mobile gaming is associated with social withdrawal, reduced empathy, emotional dysregulation, and increased aggression among children. Conclusion: However, several studies also reported adaptive emotional outcomes when gaming occurred within controlled and supervised environments. These findings highlight the importance of preventive interventions, parental supervision, and the development of educational and socially constructive game content to minimize risks for elementary school-aged children.